White Lies in Hand: Are Other-Oriented Lies Modified by Hand Gestures? Possibly Not - Cantarero, Katarzyna; Parzuchowski, Michal; Dukala, Karolina (Frontiers in Psychology, 2017)
Previous studies have shown that the hand-over-heart gesture is related to being more honest as opposed to using self-centred dishonesty. We assumed that the hand-over-heart gesture would also relate to other-oriented dishonesty, though the latter differs highly from self-centred lying. In Study 1 (N = 83), we showed that performing a hand-over-heart gesture diminished the tendency to use other-oriented white lies and that the fingers crossed behind one’s back gesture was not related to higher dishonesty. We then pre-registered and conducted Study 2 (N = 88), which was designed following higher methodological standards than Study 1. Contrary, to the findings of Study 1, we found that using the hand-over-heart gesture did not result in refraining from using other-oriented white lies. We discuss the findings of this failed replication indicating the importance of strict methodological guidelines in conducting research and also reflect on relatively small effect sizes related to some findings in embodied cognition.